Assessment of post-harvest fish losses in two selected lakes of Amhara Region, Northern Ethiopia. Issue 11 (November 2018) - Assefa, Ayalew; Abunna, Fufa; Biset, Wubet; Leta, Samson
Abstract: Fisheries play a significant role in food security, livelihood, and source of income in developing countries. The annual fish production potential of Ethiopia reaches up to 51, 000 tones, however, the actual production is much less than the potential that the country has. The fisheries sector of Ethiopian is not well developed regarding pre and post-harvest handling practices. Besides, post-harvest loss in the fisheries sector is not yet well-studied. This study objective aims to assess causes and extent of post-harvest loss associated with fish in Lakes of Hayq and Tekeze. Post-harvest loss assessment was conducted using a simple random sampling approach from October 2017 to May 2018. The study was conducted based on FAO recommendations of qualitative and quantitative field assessment methods. These methods include Informal fish loss assessment method (IFLAM), load tracking (LT) and the questionnaire loss assessment method (QLAM) methods were used to assess the causes and to estimate the amount of PHL of fish. The data generated by these methods were analyzed descriptively as well as a GLM model was used to understand the causes of fish loss in the two study lakes. A total of 140 randomly selected participants were included in the interview process. From these participants, 85 of them were from lake Tekeze while the rest were from Hayq. Results indicate that high environmental temperature, absence or delayed marketing, harvesting immature fish, predators, and flood are the most important causes of post-harvest loss of fish in the two Lakes. Besides a GLM model predicted that study lake, boat type used, boat ownership, species of fish harvested, preservation method used, distance to market (Km), Maximum catch/day (Kg), Minimum catch/day (Kg), and Fishing experience were essential predictors for post-harvest loss incurred by fishermen on daily basis. Based on secondary data from agricultural office, the monetary value of the post-harvest loss of fish was estimated to be 10, 934, 000 Ethiopian birrs (397, 600 USD) for the last six years in the study areas. A considerable product loss in the fisheries sector indicates the need for intervention by stakeholders. Provision of support services and assets such as freezers, electricity generators, boats, legal net and on job training about proper handling practices may play a tremendous role in decreasing post-harvest loss in the fisheries sector of the study areas.